Employing One’s "Talents": The Power of Innovative Bond Transactions to Finance Catholic Nonprofits - Blain, Christopher (Journal of Law and Commerce, 2015)
This article discusses such new and innovative methods of bond financing that utilize unique security devices and repayment techniques in order to provide financing to nonprofit entities that otherwise would not have had access to capital on favorable terms. In Part I, this article will discuss how Catholic conduit mortgage bonds compare to more common municipal bonds, the specific terms of Conduit Mortgage Bonds, and offer a case study intended to demonstrate the mechanics of these bonds. Part II will discuss the comparative advantages of the Endowment Funding Program, explain the role of bond financing in the Program, and provide another case study. Part III will explain how the LIFT Bond Program is being used to facilitate structured giving—again with a focus on the role of bond financing as part of the Program—and analyze its role as one component in the larger Endowment Funding Program. Finally, Part IV will discuss the newest developments in the realm of Catholic conduit mortgage bonds.